Formation and Characterization of Ultra-Sensitive Surface Plasmon Resonance Sensor Based Upon a Nano-Scale Corrugated Multi-Layered Coated D-Shaped Optical Fiber - Kalli, Kyriacos; Allsop, Thomas P.; Neal, Ron M.; Mou, Chengbo; Saied, Sayah O.; Rehman, Saeed Ur; Webb, David; Culverhouse, Phil F.; Sullivan, John L.; Bennion, Ian (My University, 2012)
We present experimental results on the performance of a series of coated, D-shaped optical fiber sensors that display high spectral sensitivities to external refractive index. Sensitivity to the chosen index regime and oupling of the fiber core mode to the surface plasmon resonance (SPR) is enhanced by using specific materials as part of a multi-layered coating. We present strong evidence that this effect is enhanced by post ultraviolet radiation of the lamellar coating that results in the formation of a nano-scale surface relief corrugation structure, which generates an index perturbation within the fiber core that in turn enhances the coupling. We have found reasonable agreement when we modeling the fiber device. It was found that the SPR devices operate in air with high coupling efficiency in excess of 40 dB with spectral sensitivities that outperform a typical long period grating, with one device yielding a wavelength spectral sensitivity of 12000 nm/RIU in the important aqueous index regime. The devices generate SPRs over a very large wavelength range, (visible to 2 µm) by alternating the polarization state of the illuminating light.
Keywords: Fiber optics; Optical fibers; Spectroscopy; Ultraviolet radiation